2021
DOI: 10.22146/ijc.61462
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Caffeic Acid in Ethanolic Extract of Spent Coffee Grounds by High-Performance Liquid Chromatography with UV Detection

Abstract: We developed a method for determining the caffeic acid in spent coffee grounds. The spent coffee ground solution was prepared by blending 3 g spent coffee grounds with 60 mL ethanol/water (40/60 v/v) for 2 h on a hot plate magnetic stirrer (60 °C, 350 rpm). The mixture was filtered and the filtrate was concentrated under vacuum (60 °C) to 5 mL. The method employed a reversed-phase high-performance liquid chromatography with a UV detector. We used a Phenomenex Luna column (250 × 4.6 mm; i.d., 5 µm) under isocra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…With a molecular weight of 180 Da, caffeic acid could serve as a potent fragment to be developed further [7], as well as a lead compound to discover more natural products in the structure-based virtual screening (SBVS) campaigns targeting DPP4. On the other hand, our effort to quantify caffeic acid in spent ground coffee (SGC) identified that SCG contains 0.17%±0.006 (w/w) of caffeic acid [8]. Recycling SCG from waste to glucose-controlling products benefiting from the caffeic acid content could be part of the near-future T2DM management.…”
Section: Introductionmentioning
confidence: 99%
“…With a molecular weight of 180 Da, caffeic acid could serve as a potent fragment to be developed further [7], as well as a lead compound to discover more natural products in the structure-based virtual screening (SBVS) campaigns targeting DPP4. On the other hand, our effort to quantify caffeic acid in spent ground coffee (SGC) identified that SCG contains 0.17%±0.006 (w/w) of caffeic acid [8]. Recycling SCG from waste to glucose-controlling products benefiting from the caffeic acid content could be part of the near-future T2DM management.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of standard caffeic acid and sample were developed according to the previous study [10]. Stock solutions of caffeic acid were prepared in methanol solvent.…”
Section: Standard Caffeic Acid and Sample Preparationmentioning
confidence: 99%
“…Caffeic acid, (E)-3-(3,4-dihydroxyphenyl)prop-2-enoic acid, is a phenolic compound that has widely been found in several agricultural products such as vegetables, fruits, carrots, tea, coffee beans, and spent coffee grounds [9,10]. Several experiments have…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid, a natural product which belongs to the phenolic family, has a wide range of biological activities such as antidiabetic, antioxidant, anti-inflammatory, and anti-carcinogenic [6], [7]. Caffeic acid could be synthesized and extracted from plant tissues such as fruits, potatoes, coffee beans, and even spent coffee grounds [8]- [10]. Previous research found that caffeic acid could potentially be an inhibitor of dipeptidyl peptidase IV (DPP4), a well-known target in drug discovery for treating type-2 diabetes mellitus [11].…”
Section: Introductionmentioning
confidence: 99%